1999
DOI: 10.1099/00221287-145-9-2549
|View full text |Cite
|
Sign up to set email alerts
|

Tellurite-mediated thiol oxidation in Escherichia coli

Abstract: 2N3 ), is toxic to most micro-organisms, particularly Gram-negative bacteria. The mechanism of tellurite toxicity is presently unknown. Many heavy metals and oxyanions, including tellurite, interact with reduced thiols (RSH). To determine if tellurite interaction with RSH groups is involved in the toxicity mechanism, the RSH content of Escherichia coli cultures was assayed. After exposure to tellurite, cells were harvested and lysed in the presence of the RSH-specific reagent 5,5'-dithiobis(2-nitrobenzoic acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
142
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 129 publications
(148 citation statements)
references
References 52 publications
6
142
0
Order By: Relevance
“…As was observed by Turner et al (1999Turner et al ( , 2001) tellurite causes thiol oxidation, compromising seriously the redox balance of the cell. Moreover, superoxide generated as byproduct of tellurite reduction (Pérez et al, 2007) (Massey, 1994;Messner & Imlay, 1999, 2002.…”
Section: Discussionmentioning
confidence: 99%
“…As was observed by Turner et al (1999Turner et al ( , 2001) tellurite causes thiol oxidation, compromising seriously the redox balance of the cell. Moreover, superoxide generated as byproduct of tellurite reduction (Pérez et al, 2007) (Massey, 1994;Messner & Imlay, 1999, 2002.…”
Section: Discussionmentioning
confidence: 99%
“…Among the highly induced genes implicated in oxidative stress resistance are the catalase gene katE (DR1998), terB (DR2220), terZ (DR2224), msrA (DR1849), dps2 (DRB0092) (602), and five genes of the Nudix hydrolase family, including the MutT ortholog (368). The tellurium resistance proteins TerB and TerZ maintain the intracellular reducing environment in E. coli, possibly by directly reversing disulfide bonds (626), and confer resistance to various damaging agents, such as heavy metal ions, MMS, MMC, and UV radiation (31). MsrA is a methionine sulfoxide reductase, while Dps2 is a DNA binding protein, which presumably protects DNA from oxidative damage (11,390,668).…”
Section: Induction Of Gene Expression and Protein Synthesis In Responmentioning
confidence: 99%
“…These results suggested that YqhD may play an antioxidant role by protecting E. coli from the oxidative damage caused specifically by ROS. This YqhD function would be of particular importance when cells encounter compounds that generate superoxide (tellurite) or hydroxyl radicals (chromate) (4, 5) since these toxics also affect cytoplasmic GSH levels (9,29,30). In this context, the hypersensitive phenotype to K 2 TeO 3 and K 2 Cr 2 O 7 observed in E. coli ⌬yqhD could be explained by a dual effect caused by ROS, namely the known direct damage on proteins, DNA, and membrane lipids and, indirectly, the inherent toxicity of peroxides and reactive aldehydes generated by membrane lipid peroxidation, which could not be scavenged in the absence of GSH.…”
Section: Figure 3 Oxidized Proteins In E Coli a Sds-page Showing mentioning
confidence: 99%